Innovative Solutions for a Circular Economy: a Review on Waste to Chemicals Valorization Plants - Antonio Trinca; Luca Di Palma; Nicola Verdone (Chemical engineering transactions, 2024)
Global concerns over fossil fuel dependence drive biomass use for fuel and chemical production. The goal is to develop conversion methodologies that make bio-based products competitive with petroleum-based ones. This review examines recent advances in biomass conversion processes, including both thermochemical and biochemical techniques. The selection of the most suitable conversion technique depends on biomass availability and the end goal. Currently, the focus is on developing catalysts and optimizing process parameters to make conversion technologies more efficient. Although some technologies are already commercialized, methods to process lignocellulosic and marine biomasses are still under development. In addition, significant resources are being devoted to optimizing processes to extract basic chemicals from biomass, consolidating the biorefinery concept. This review illustrates the main developments in these directions.